2017
DOI: 10.1590/1806-9282.63.01.43
|View full text |Cite
|
Sign up to set email alerts
|

The P-A-C-I-E-N-T-E Protocol: An instrument for breaking bad news adapted to the Brazilian medical reality

Abstract: Objective: There are plenty of published tools for breaking bad medical news; however, none of them is culturally appropriate to our reality or published in the Brazilian literature. This study proposes a genuinely Brazilian communication tool and evaluates its acceptance among doctors and nurses. Method: This was a prospective study. The data were collected after specific training of doctors and nurses on the bad news communication techniques based on the P-A-C-I-E-N-T-E ("patient," in Portuguese) Protocol. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
25

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 35 publications
3
33
0
25
Order By: Relevance
“…The University of Botswana medical students all reported attending a communication lecture during their second year of training, which was higher than other studies that showed only 44%-62% having received prior training on breaking bad news (Baile et al, 2000;Jameel et al, 2012;Pereira et al, 2017). The medical students had low levels of perceived competence in their ability to break bad news before the workshop, with only 23% of those participating rating their skills "good" or "very good," which was similar to other studies that report 15%-53% (Baile et al, 2000;Jameel et al, 2012;Pereira et al, 2017). The University of Botswana students perceived competence in their ability to break bad news increased from 23% to 85% after the workshop, which was similar to that in a Pakistan study that showed an increase from 15% to 64% (Jameel et al, 2012).…”
Section: Discussionmentioning
confidence: 83%
“…The University of Botswana medical students all reported attending a communication lecture during their second year of training, which was higher than other studies that showed only 44%-62% having received prior training on breaking bad news (Baile et al, 2000;Jameel et al, 2012;Pereira et al, 2017). The medical students had low levels of perceived competence in their ability to break bad news before the workshop, with only 23% of those participating rating their skills "good" or "very good," which was similar to other studies that report 15%-53% (Baile et al, 2000;Jameel et al, 2012;Pereira et al, 2017). The University of Botswana students perceived competence in their ability to break bad news increased from 23% to 85% after the workshop, which was similar to that in a Pakistan study that showed an increase from 15% to 64% (Jameel et al, 2012).…”
Section: Discussionmentioning
confidence: 83%
“…Effective BBN process requires effective communication skills [20], expressing empathy, and trust [21]. Pereira, Calônego, Lemonica, and Barros [22] mentioned that communication-training program should be added to the curriculum of each organization before entering the clinical field. Furthermore, they suggest preparing of healthcare providers through training programs that contain guidance for cognitive and behavioral coping strategies that can deal with any adverse reactions, which may came from patients or their families [23].…”
Section: Introductionmentioning
confidence: 99%
“…No Protocolo PACIENTE encontra-se o acréscimo de um passo em relação ao Protocolo SPIKES, intitulado de: Não Abandone o Paciente. Neste passo adicional é proposto que o profissional de saúde se responsabilize com o cuidado do paciente, seja qual for o desfecho final de saúde (Pereira et al, 2017). Este último passo é fundamental quando se pensa na abordagem de Cuidados Paliativos, onde tem-se um olhar para o sujeito em vez da doença e se pensa em estratégias de alívio de sintomas (ANCP, 2012).…”
Section: Resultsunclassified
“…Um estudo realizado com médicos e enfermeiros sobre o processo da comunicação de más notícias indicou que discutir o fim de tratamentos curativos, falar sobre a recidiva da doença e convidar a rede de apoio do paciente para a comunicação são algumas das dificuldades percebidas na comunicação de más notícias (Pereira et al, 2017). Prognósticos não favoráveis e que indicam um desfecho negativo em saúde também são apontados na literatura como um aspecto difícil a ser comunicado (Calsavara et al, 2019).…”
Section: Resultsunclassified
See 1 more Smart Citation